Improving Science Learning Activities And Outcomes Basic Competencies Identifying The Solar System And Characteristics Of Members Of The Solar System ( Bintang) Through Power Point Based Learning Media For Class VI Students Of SD Negeri 1 Kemudo Prambanan District Semester I Academic Year 2021/2022 - Sittah Nur Hayati (Universitas Sebelas Maret, 2022)
Increased science learning activities and outcomes in the basic competency of identifying the solar system and the characteristics of the members of the solar system (stars) for class VI students at SD Negeri 1 Kemudo Semester I for the 2021/2022 academic year. The aim of this research is to improve science learning outcomes in the basic competency of identifying the solar system and the characteristics of the members of the solar system (stars) through Power Point-based learning media. Data collection tools in the form of tests are needed to measure the level of achievement of actions as a learning resource in improving learning outcomes in science subjects. Documentation is used to collect data about events or happenings which include the planning, implementation, evaluation observation and reflection stages using photos as reports and evidence in this research. The observation method was chosen for data collection in this research. The research results showed that in cycle II, student activity in learning had increased. Student activity in cycle I reached 68.33% with the criteria of being active enough. In cycle II, student activity increased to 78.53% with active criteria.